Parents’ attitudes in Makkah towards the use of modern technology by their children in the light of some demographic variables - Alhilabi, Bakhita Mubarak (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the attitudes of parents in the city of Makkah towards their children’s use of modern technology in the light of some demographic variables. On the study sample, the results showed that parents’ attitudes towards their children’s use of modern technology came at a high level, with an arithmetic average (3.79), and a percentage (79.4%), and after the impact of modern technology on social aspects, it ranked first with an arithmetic average (4.06). with a percentage (81%), while it ranked second after the impact of modern technology on health aspects, with an arithmetic average (4.0), and with a percentage (80%), and came in third place after the impact of modern technology on educational aspects, and with an arithmetic average (3.98)), with a percentage of (79.6%), and came in the fourth and last place after the impact of modern technology on the economic aspects, with a mean of (3.83), and with a percentage of (76.6%). The results also showed that there were statistically significant differences between the averages of parents’ attitudes in the city of Makkah Al-Mukarramah towards their children’s use of modern technology due to the variable of the gender of the guardian. 54.55%) and indicates the homogeneity of the sample from the middle stage, males ranged from frequency (152) and percentage (53.14%) and for females with frequency (134) and percentage (47.00%), and the homogeneity of the sample from the secondary stage of males ranged from frequency (121) and percentage (46%)) and from females with a frequency of (143) and a percentage of (54.00%)، The results also showed that there were statistically significant differences between the averages of parents’ attitudes in the city of Makkah towards their children’s use of modern technology and its effects due to the variable of the guardian’s gender and in favor of the parents. school for students, and for the benefit of parents of middle school students.